Causal association between serum total bilirubin and cholelithiasis: a bidirectional two-sample Mendelian randomization study - Sun, Yang; Yang, Shaojie; Dai, Wanlin; Zheng, Zhuyuan; Zhang, Xiaolin; Zheng, Yuting; Wang, Jingnan; Bi, Shiyuan; Duan, Yunlong; Wu, Shuodong; Kong, Jing (Frontiers in Endocrinology, 2023)
Background Observational studies about the association between serum total bilirubin and cholelithiasis are inconsistent. Hence, it is essential to reevaluate the association between serum total bilirubin and cholelithiasis and to verify whether such association is causal or not. Methods We selected single-nucleotide polymorphisms (SNPs) that are strongly associated with exposure as instrumental variable and conducted a bidirectional two-sample Mendelian randomization (MR) study to explore the causal association between serum total bilirubin and cholelithiasis. We implemented the inverse-variance weighted approach as a primary analysis to combine the Wald ratio estimates. Four additional analyses, namely, MR-Egger regression, weighted median, weighted mode, and MR–pleiotropy residual sum and outlier (PRESSO), were utilized to investigate the causal association and the influence of potential pleiotropy. Results A total of 116 SNPs were selected as valid instrumental variables to estimate the causal association of serum total bilirubin on cholelithiasis, and causal association between genetically determined serum total bilirubin and cholelithiasis was demonstrated [beta = 0.10; 95% confident interval (CI), 0.07 to 0.14; p < 0.001]. Likewise, the other methods, namely, the weighted median (beta = 0.12; 95% CI, 0.08 to 0.15; p < 0.001), MR-Egger (beta = 0.11; 95% CI, 0.08 to 0.15; p < 0.001), weighted mode (beta = 0.11; 95% CI, 0.08 to 0.15; p < 0.001), and MR-PRESSO approaches, further confirmed that this result (p = 0.054) indicates similar results. In addition, seven SNPs were selected as instrumental variable to estimate causal association of cholelithiasis on serum total bilirubin, and the result supported the causal effect of cholelithiasis to serum total bilirubin (beta = 0.12; 95% CI, 0.09 to 0.15; p < 0.001). At the same time, the other methods, namely, the weighted median (beta = 0.10; 95% CI, 0.06 to 0.13; p < 0.001), MR-Egger (beta = 0.12; 95% CI, 0.07 to 0.18; p = 0.007), weighted mode (beta = 0.09; 95% CI, 0.03 to 0.14, p = 0.019), and MR-PRESSO methods, further confirmed this result (p < 0.001). Conclusion Our MR study revealed that the serum total bilirubin was causally associated with the risk of cholelithiasis, and the genetic predisposition to cholelithiasis was causally associated with the increased serum total bilirubin levels.